Hematopoietic Stem Cell Transplantation for Adult Acute Lymphoblastic Leukaemia - Piccaluga, Pier Paolo; Paolini, Stefania; Bonifazi, Francesca; Bandini, Giuseppe; Visani, Giuseppe; Giebel, Sebastian (IntechOpen, 2012)
None